Hallmarks of frailty and osteosarcopenia in prematurely aged PolgA(D257A/D257A) mice - Ariane C. Scheuren; Gommaar D'Hulst; Gisela A. Kuhn; Evi Masschelein; Esther Wehrle; Katrien De Bock; Ralph Müller (Wiley, 2020)
Abstract Background Frailty is a geriatric syndrome characterized by increased susceptibility to adverse health outcomes. One major determinant thereof is the gradual weakening of the musculoskeletal system and the associated osteosarcopenia. To improve our understanding of the underlying pathophysiology and, more importantly, to test potential interventions aimed at counteracting frailty, suitable animal models are needed. Methods To evaluate the relevance of prematurely aged PolgA(D257A/D257A) mice as a model for frailty and osteosarcopenia, we quantified the clinical mouse frailty index in PolgA(D257A/D257A) and wild‐type littermates (PolgA(+/+), WT) with age and concertedly assessed the quantity and quality of bone and muscle tissue. Lastly, the anabolic responsiveness of skeletal muscle, muscle progenitors, and bone was assessed. Results PolgA(D257A/D257A) accumulated health deficits at a higher rate compared with WT, resulting in a higher frailty index at 40 and 46 weeks of age (+166%, +278%, P < 0.0001), respectively, with no differences between genotypes at 34 weeks. Concomitantly, PolgA(D257A/D257A) displayed progressive musculoskeletal deterioration such as reduced bone and muscle mass as well as impaired functionality thereof. In addition to lower muscle weights (−14%, P < 0.05, −23%, P < 0.0001) and fibre area (−20%, P < 0.05, −22%, P < 0.0001) at 40 and 46 weeks, respectively, PolgA(D257A/D257A) showed impairments in grip strength and concentric muscle forces (P < 0.05). PolgA(D257A/D257A) mutation altered the acute response to various anabolic stimuli in skeletal muscle and muscle progenitors. While PolgA(D257A/D257A) muscles were hypersensitive to eccentric contractions as well as leucine administration, shown by larger downstream signalling response of the mechanistic target of rapamycin complex 1, myogenic progenitors cultured in vitro showed severe anabolic resistance to leucine and robust impairments in cell proliferation. Longitudinal micro‐computed tomography analysis of the sixth caudal vertebrae showed that PolgA(D257A/D257A) had lower bone morphometric parameters (e.g. bone volume fraction, trabecular, and cortical thickness, P < 0.05) as well as reduced remodelling activities (e.g. bone formation and resorption rate, P < 0.05) compared with WT. When subjected to 4 weeks of cyclic loading, young but not aged PolgA(D257A/D257A) caudal vertebrae showed load‐induced bone adaptation, suggesting reduced mechanosensitivity with age. Conclusions PolgA(D257A/D257A) mutation leads to hallmarks of age‐related frailty and osteosarcopenia and provides a powerful model to better understand the relationship between frailty and the aging musculoskeletal system.